Proceedings of the National Conference on Computer Graphics and Multimedia, 7th-9th October 2002, Equatorial Hotel, Melaka - National Conference on Computer Graphics and Multimedia 2002 (CoGRAMM '02) (2002 : Melaka); Universiti Teknologi Malaysia; Chief Minister of Melaka's Department (Skudai : Penerbit Universiti Teknologi Malaysia, 2002)
20